การบริหารทรัพยากรกายภาพสำหรับทรัพย์ส่วนกลางประเภทสิ่งอำนวยความสะดวกของอาคารชุดพักอาศัยระดับราคาปานกลางในเขตกรุงเทพชั้นใน - ปรางค์วดี ภู่พกสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
A lot of research shows that medium-price residential condominiums have faced one common problem the share facility assets are typically inferior and broken. For this reason, the purpose of this thesis is to examine the present situation and problem. The study methods are interviews and research by which interviews were conducted with the people involved in the business, namely co-owners and condo managers as well as relevant documents which were researched. The study cases of this thesis are 22 medium-price residential condominiums age 5 years or older located in the inner area of BKK. In the paper, most of residential condominiums are housing. Only five residential condominiums have been used together with service apartment, hotel and/or business office which means generally the building’s share facility assets are used by both residents and other people. According to a survey, Most residential condominiums have good share facility assets only a few residential condominiums have poor share facility assets. This is because most residential condominiums have been maintained and repaired. The condominiums that retain poor share facility assets are; Cha-learn-pol (21 years old), Ratchatavee Tower (19 years old), Pratumwan Place (18 years old), and Family Condominium (15 years old) where poor share facility assets are as a result of the age of the buildings. At Sai-tarn Condominium, Pra-tu-num Place, and Tarn win Place the poor share facility assets are as a result of insufficient maintenance budget. Compared to property of a similar age, Julladit Tower (16 years old) has good share facility assets as a result of good maintenance. Interestingly, Royal Nine Residence, Julladit Tower, Ka-samesun I, and Green Peace Mansion though used by quite a number of residents, their share facility assets remains good as a result of good maintenance. A survey also found that Petch 9 Tower, Tunyakarn, Sum-larn mansion building, Dee-Dee Tower, and Noble House Prayatai have hired professional companies to manage and maintain the buildings. Grand Diamond Pra-tu-num, Supalai Place, Sri-wa-la Mansion II, Garden Place Ratchada, and Du-ri-yank Charisma allow outsiders or non-residents to use their space so that they can earn more for the building maintenance budget. This paper therefore concludes that the efficiency in resource management leads to better share facility assets and their maintenance in residential condominiums.